Exploring Effectiveness of ACE Cycle of Instruction on Teaching area and Volume of Cylinder - Chhetri, Deb Bahadur (Interdisciplinary Issues in Education, 2023)
This article aimed to explore the effectiveness of the application of activities, classroom discussion and exercise (ACE) cycle in mathematics instruction and investigate students' perceptions of the ACE cycle of teaching. The study focused on the area and volume of cylinders and was conducted among 20 students in grade nine selected for the intervention. The study adopted the APOS (Action, Process, and Object Schema) theory as the guiding theory and the ACE teaching cycle for intervention and implemented it over only one week. The study's results revealed that the well-planned three phases of the ACE cycle of instruction were effective in promoting students' activeness, developing their understanding of the area and volume of the cylinder, enhancing their motivation and improving their achievement.